A Novel Fluorescence Probe for the Reversible Detection of Bisulfite and Hydrogen Peroxide Pair in Vitro and in Vivo. Issue 21 (12th September 2021) - Wang, Yue; Zhou, Fang; Meng, Qingtao; Zhang, Songhe; Jia, Hongmin; Wang, Cuiping; Zhang, Run; Zhang, Zhiqiang
Abstract: The detection of changes in the reactive oxygen species (ROS)/reactive sulfur species (RSS) couple is important for studying the cellular redox state. Herein, we developed a 1, 8‐naphthalimide‐based fluorescence probe (NI ) for the reversible detection of bisulfite (HSO3 − ) and hydrogen peroxide (H2 O2 ) in vitro and in vivo . NI has been designed with a reactive ethylene unit which specifically reacts with HSO3 − by a Michael addition reaction mechanism, resulting in the quenching of yellow fluorescence at 580 nm and the appearing of green fluorescence at 510 nm upon excitation at 500 nm and 430 nm, respectively. The addition product (NI−HSO3 ) could be specifically oxidized to form the original C=C bond of NI, recovering the fluorescence emission and color. The detection limits of NI for HSO3 − and NI−HSO3 for H2 O2 were calculated to be 2.05 μM and 4.23 μM, respectively. The reversible fluorescence response of NI towards HSO3 − /H2 O2 couple can be repeated for at least five times. NI is reliable at a broad pH range (pH 3.0–11.5) and features outstanding selectivity, which enabled its practical applications in biological and food samples. Monitoring the reversible and dynamic inter‐conversion between HSO3 − and H2 O2 in vitro and in vivo has been verified by fluorescence imaging in live HeLa cells, adult zebrafish and nude mice. Moreover, NI has been successfully applied to detect of HSO3 − levels in food samples. Abstract : We have developed a 1, 8‐naphthalimide‐based fluorescence probe (NI) for monitoring of the HSO3 − /H2 O2 regulated cycle. The reversible response was realized by HSO3 − ‐involved 1, 4‐addition and H2 O2 ‐induced elimination reaction with C=C double bond of NI . Monitoring the reversible and dynamic inter‐conversion between HSO3 − and H2 O2 in vitro and in vivo has been verified by fluorescence imaging in live HeLa cells, adult zebrafish and nude mice. The successful applications of NI prove that it would be a useful tool for a range of redox‐related physiological and pathological investigations in the future.